Kemampuan Membaca Pemahaman Siswa Kelas XI SMA Negeri 2 Kaur - Akbar, Yandi; Wulandari, Catur; Arifin, M. (Jurnal Korpus, 2025)
Abstract This study set out to ascertain the reading comprehension skills of SMA Negeri 2 Kaur's class XI pupils. In this work, a descriptive method with a quantitative approach was employed. The study's population consisted of 153 students from six classes in class XI at SMA Negeri 2 Kaur, 71 of whom were male and 82 of whom were female. A random sample procedure was utilized in this study to choose participants; 24 students, or 11% of the total, were chosen. The Student Reading Comprehension Ability Test was used as the method for gathering data. According to the study's findings, the average score for reading comprehension in Indonesian was 87.5 with a high understanding category, the ability to read comprehension in Biology with an average of 85.00 with a high understanding category, the ability to read comprehension in Islamic Religious Education with a value of 85.00 with a good category, and the ability to read comprehension in Geography with a value of 85.00 with a good ability category. From the overall results, students generally showed good reading comprehension abilities in all fields of study tested. The average value ranges between 85-87.5. Keywords: ability reading comprehension, of students of SMAN 2 Kaur.